Nutrition and healthy aging: Dietary strategies for promoting longevity (International Seven Journal of Multidisciplinary, 2024)
As the population ages, nutritional needs change, and maintaining an adequate diet can become a complex task for many seniors. In the United States, the number of people aged 65 and over has grown significantly, from 37.8 million in 2007 to 50.9 million in 2017, and is expected to reach 94.7 million by 2060. With increasing longevity, the elderly are more vulnerable to age-related chronic diseases. According to the Centers for Disease Control and Prevention, approximately 28.1% of elderly Americans suffer from heart disease, 26.8% have diabetes, and 19.3% are diagnosed with cancer.